ANALISIS PROSES PEMBELAJARAN BIOLOGI PADA MATERI SISTEM PEREDARAN DARAH DALAM PELAKSANAAN KURIKULUM 2013 DI MA KOTA TANGERANG SELATAN - Raisa Amalia Novitri (Journal of Innovation Research and Knowledge, 2023)
The research aimed to describe the implementation of biology learning process on circulatory system topic in Madrasa South Tangerang City. This research was conducted in three Madrasa in South Tangerang City namely Sekolah A, Sekolah B, and Sekolah C in academic year 2019/2020. This type of research is descriptive research with a qualitative approach. The technique sampling is proporionate stratified random sampling. The sample of the study consisted of three biology teachers of Class XI MIA. The data was collected through observation, interview, and, checklist. Data were analyzed using the reduction step, data presentation, and concluding. The results showed that the implementation of Circulatory System learning has not been done well in these three schools.